2014
DOI: 10.1097/aap.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fascia Iliaca Compartment Block for Positioning Patients With Hip Fractures for Central Nervous Blockade

Abstract: Performing an FICB before positioning for SA provides superior pain management compared with IVFE administration, facilitates spinal performance, and yields satisfactory postoperative analgesia and wide patient acceptance, hence improving overall quality and efficiency of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 27 publications
1
63
0
1
Order By: Relevance
“…Guay et al [9] included seven studies and 285 participants and reported that peripheral nerve block, administered as a single shot or continuous block, resulted in less postoperative opioid requirements compared to no nerve block. Diakomi et al [37] compared FINB to IVA to facilitate positioning for femur fracture patients under spinal block. Their study results also showed that FINB had lower opioid requirements than IVA.…”
Section: Discussionmentioning
confidence: 99%
“…Guay et al [9] included seven studies and 285 participants and reported that peripheral nerve block, administered as a single shot or continuous block, resulted in less postoperative opioid requirements compared to no nerve block. Diakomi et al [37] compared FINB to IVA to facilitate positioning for femur fracture patients under spinal block. Their study results also showed that FINB had lower opioid requirements than IVA.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nerve blocks has been shown to increase hip flexion following hip fracture, and enable patients to sit more comfortably . Blocks have also been shown to reduce pain during positioning for spinal anaesthesia .…”
Section: Methodsmentioning
confidence: 99%
“…All patients who received a nerve block indicated that they would prefer to receive the same management in the event of a future operation, compared with only 25% of those who received i.v. fentanyl . Table provides an itemised summary of the prospective, randomised controlled studies published to date.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, CFICB was associated with greater patient satisfaction, which was consistent with the results of Candal-Couto et al (23) and Dulaney-Cripe et al (24). Diakomi et al (31) concluded that performing an FICB prior to positioning for spinal anesthesia provided superior pain management compared with intravenous fentanyl administration facilitated spinal performance. According to Diakomi et al (31) and the present study, FICB provided superior analgesia not only prior to positioning for spinal anesthesia but also during the preoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Diakomi et al (31) concluded that performing an FICB prior to positioning for spinal anesthesia provided superior pain management compared with intravenous fentanyl administration facilitated spinal performance. According to Diakomi et al (31) and the present study, FICB provided superior analgesia not only prior to positioning for spinal anesthesia but also during the preoperative period. The study group in the present study did not develop CFICB-associated complications.…”
Section: Discussionmentioning
confidence: 99%